2013
DOI: 10.1186/1479-5876-11-146
|View full text |Cite
|
Sign up to set email alerts
|

Complementary serum proteomic analysis of autoimmune hepatitis in mice and patients

Abstract: BackgroundAutoimmune hepatitis (AIH) is a chronic liver disease caused by inflammation of the liver. The etiology of AIH remains elusive, and there are no reliable serum biomarkers.MethodsIn order to identify candidate biomarkers, 2-DE analysis of serum proteins was performed using a mouse model of AIH induced by treatment with concanavalin A (ConA). To enrich samples for low abundance molecules a commercial albumin removal reagent was used. In an independent analysis, candidate biomarkers were identified in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…However, the results also showed that most of albumin and IgG were removed except few of them (Fig. 1), which is consistent with manufacturer’s instruction and previous study [26].
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the results also showed that most of albumin and IgG were removed except few of them (Fig. 1), which is consistent with manufacturer’s instruction and previous study [26].
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…This shows that a relative amount of IgG was still present in the IgG-depleted plasma samples [26]. Oxidative stress alters its structure and may result in modification of its biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…122642, Calbiochem, San Diego, CA) according to user protocols. The main high-abundant proteins, including albumin and IgG proteins, were efficiently deleted with this kit, which had been reported in our previous paper [19]. The pretreated serum sample was precipitated by adding 4 × volume of ice-cold acetone at -20℃ overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Being clotted for 2h at room temperature, the supernatant serum from 5ml blood was collected by centrifugation at 3000 rpm for 15min [19]. 100μL serum was used for ELISA analysis to compare PGRMC1 concentration between RCC patients and healthy persons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation